(3fXGe GdVQGFH aj GdESdGe heOi JWHjbg aj GdeedcI GdYQHjI GdSYhOjI (B:s (3eY GdebGQfI (B/ s - (3YHO GdYRjR GdYdj GdUGdM GdfYjes; (3RcQjG GdHQjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 1974)
(3JfbSe GdQSGdI Edi CQHYI CHhGH; ajJfGhd GdHGH GdChd MbjbI GdVQjHI hfXGegG, hGdHGH GdKGfj Yf TQjYI GdVQGFH hCZQGVgG hbhGYOgG, HjfeG jJfGhd GdHGH GdKGdK GdCfhGY GdQFjSjI ddVQjHI GdESdGejI hLHGjJgG, hCNjQG GdHGH GdQGHY GdPj jJfGhd JWHjbGJ GdVQjHI aj GdeedcI GdYQHjI GdSYhOjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1974.s
(3HHdjhLQGajG(B: (3UaMGJ (B613-622.s
Keywords: (3CZQGV GdVQjHIs; (3GdVQGFH GdTNUjIs; (3GdYThQs; (3GdLRjIs; (3GdNQGLs; (3GdLHGjIs; (3GdWhGHY GdeGdjIs; (3VQjHI GdLgGOs; (3VQjHI GdONds; (3CZQGV GdVQjHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs